The dual face of power: alienation and its Overcoming in Marx, Arendt and Rosa - Sordelli, Christian Alejandro (2026)
The article develops a comparative theoreticalconceptual analysis of the ambivalence of power as both a source of alienation and a condition for its overcoming, based on the proposals of Karl Marx, Hannah Arendt, and Hartmut Rosa. First, it offers a conceptual framework that defines alienation as a socially produced and defective mode of relation between the subject and the world, distinguishing subjective, structural, and ideologicalsymbolic levels. Second, it reconstructs the Marxist conception of the power of capital as an objectified power that organizes class exploitation and produces paradigmatic forms of alienation, as well as the idea of a collectively reappropriated social power. It then examines Arendt’s conception of power as action in common, distinct from violence, and her diagnosis of world alienation through the figures of the animal laborans, the homo faber, and political action. Finally, it integrates Rosa’s theory of resonance in order to update the problem of alienation as a mute or hostile relationship with the world and to conceive democracy as a sphere of political resonance, and it discusses processes of oligarchization and crisis of representation that strain the dual face of power in contemporary societies.